A longitudinal study into science learning environments in Dunedin secondary schools - Thompson, Murray Bruce (Curtin University, 2010)
Science learning environments have been studied in secondary schools around the world. There is a long history of this going back over 30 years. The study presented here is unique in that it observes a single cohort in six schools in one city over a period of three years starting from when the students began high school and following them to their first external assessment.The students were surveyed using the Science Learning Environment Inventory and a short attitude and self efficacy questionnaire. The surveys were carried out late in the year for the first two years and about mid year in the third year. The students’ total credits in NCEA science were also collected as they became available. The total data set was collated so that each student’s data set was assigned an identifying number.The data were analysed using SPSS and comparisons made between each year and the relationships between the variables such as learning environment and NCEA achievement and variation in attitude against year level.The most striking finding was that year 10 presents as an anomaly and shows result in almost all variables, which do not sit between year 9 and year 11. This does show some correlation with the anecdotal evidence of teachers that this year is the most difficult group to teach but nevertheless warrants much more investigation.